Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1111/j.1432-1033.1989.tb14682.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mRNA levels of rat pancreatic lipase in the early days of consumption of a high‐lipid diet

Abstract: The time-course response of rat pancreatic enzymes to a diet containing 25% sunflower oil was investigated. A 1.2-fold enhancement in lipase specific activity was observed as early as the first day of diet consumption and was further increased up to 1.9-fold on the 5th day. On the other hand, colipase activity was slightly decreased during the first two days of high-lipid diet intake and then increased. An immediate and direct effect was also exerted by the 25% lipid diet on lipase biosynthesis. Both fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
3
14
1
Order By: Relevance
“…This is also the first report of dietary regulation of PL in the preweaned rat, as previous studies on adaptation of PL to dietary fat all have been in weaned or adult animals. The parallel changes found in PL mRNA levels and activity in the weanling and adult rat in this study are concordant with previous studies (20,22,37) and suggest that the dietary regulation of PL postweaning is pretranslational or transcriptional. PL exhibited the previously reported (9) developmental regulation, independent of diet; PL activity and mRNA levels were low at d9 and d15 and increased to maximal levels by d28.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This is also the first report of dietary regulation of PL in the preweaned rat, as previous studies on adaptation of PL to dietary fat all have been in weaned or adult animals. The parallel changes found in PL mRNA levels and activity in the weanling and adult rat in this study are concordant with previous studies (20,22,37) and suggest that the dietary regulation of PL postweaning is pretranslational or transcriptional. PL exhibited the previously reported (9) developmental regulation, independent of diet; PL activity and mRNA levels were low at d9 and d15 and increased to maximal levels by d28.…”
supporting
confidence: 81%
“…The different amount of polyunsaturated fat in the milk and the diet did not affect expression of PLRP1. The lack of influence of amount of fat in diet on PLRP1 expression in weanling rats in this work is surprising and differs from other studies (16,20,22,37), in which PLRP1 was shown to be transcriptionally regulated by dietary fat. However, the introduction of different amounts of PUFA, started earlier during the tertiary phase of pancreatic development, may alter the long-term regulation of PLRP1.…”
contrasting
confidence: 55%
“…The regulation of PLRP1 by the amount of dietary fat is transcriptional, as demonstrated by increased nuclear transcript run-on assay (15). The parallel changes in PL mRNA levels (16) and synthetic rates (14) suggest that the regulation of PL is pretranslational and likely to be transcriptional. However, such transcriptional regulation has yet to be conclusively documented.…”
mentioning
confidence: 90%
“…The rats were fed for 7 d ad libitum purified low-(LF; 11% of energy), moderate-(MF; 40% of energy) and high-(HF; 67% of energy) fat diets with MCT (trioctanoate/tridecanoate, Neobee 1053, Stepan, Maywood, NJ) or low-fat (11% of energy) diet with safflower oil (control). The period of 7 d was selected because maximal adaptation and new steady-state levels are seen in PL content, synthesis, and mRNA levels after 5 d (14). The composition of the diets is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation